Research on Base64 Encoding Algorithm and PHP Implementation - Wen, Somchai; Dang, Wen (2018 26th International Conference on Geoinformatics, 2018)
In order to realize the data encryption of enterprise information platform, the principle of Encryption and Decryption of Base64 algorithm is expatiated and explained in detail. Through the combination of graphic narrative, so that readers can through examples of applications, quick grasp of Base64 algorithm encryption and decryption work and storage principle. At the same time combined with the actual software development process, the use of the principle of Base64 algorithm PHP to achieve the enterprise information stored in the process of data encryption and decryption function.